Numerical Simulation of Non-isothermal Turbulent Flow in a Pipe with Rheology Newtonian and Viscoplastic Fluid - Maksim A. Pakhomov; Uzak K. Zhapbasbayev (Research and Developments in Engineering Research Vol. 5, 2023)
This chapter aims to investigate the flow and heat transfer in a turbulent hydrodynamically steady-state incompressible non-Newtonian fluid flowing through a pipe. This study may be of interest to scientists and research engineers dealing with the design and transport of waxy crude oils in pipelines. Rheological properties of the fluid are described by the Herschel–Bulkley model, which implies an unyielded region formation in the flow. Viscous dissipation effects and temperature dependence of the viscosity are taken into account when simulating the process. The value of its streamwise velocity in the axial zone increased significantly when the fluid moved along the pipe. On the other hand, it fell in the vicinity of the wall, and the height of the region with zero fluid velocity rose. This happened as a result of a non-Newtonian fluid’s viscoplastic characteristics. The complexity of the numerical modeling of such flows connected to the developed turbulence models can hardly be verified directly using the experimental benchmark. It should be noted that the level of turbulence anisotropy of a non-Newtonian fluid is higher than that of a Newtonian fluid. The height of the region with a zero fluid velocity in the pipe increased gradually as the non-Newtonian fluid (waxy crude oil) moved through the pipe. A noticeable increase in the level of turbulent kinetic energy in the axial zone of the pipe and its noticeable decrease in its near-wall region were observed. In the logarithmic layer, the velocity profile for the non-Newtonian fluid had a form qualitatively similar to that of the Newtonian fluid. An excess of the axial velocity was characteristic for both types of non-Newtonian fluids with a logarithmic profile.